2020
DOI: 10.1177/0044118x20941344
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Family Socioeconomic Status and Life Satisfaction in Chinese Adolescents: The Mediating Role of Self-Esteem and Social Support

Abstract: This study aimed at examining the relationships among subjective family socioeconomic status (FSES), self-esteem (SE), social support (SS), and life satisfaction (LS) in two independent samples of Chinese adolescents. In Study 1, 510 adolescents were asked to complete a multi-section questionnaire. The mediation analyses indicated that subjective FSES predicted LS through three pathways. First, subjective FSES predicted LS through the mediating effect of SE. Second, subjective FSES predicted LS through the med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 61 publications
(105 reference statements)
6
27
0
Order By: Relevance
“…Each step is scored, and the higher the score, the higher the subjective FSES. The scale has shown good reliability [test-retest reliability = 0.76 ( 58 )] and has been used in studies conducted with Chinese adolescents ( 37 , 59 , 60 ). In this study, the Cronbach's alpha coefficient was 0.79.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Each step is scored, and the higher the score, the higher the subjective FSES. The scale has shown good reliability [test-retest reliability = 0.76 ( 58 )] and has been used in studies conducted with Chinese adolescents ( 37 , 59 , 60 ). In this study, the Cronbach's alpha coefficient was 0.79.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, in order to control for the effect of objective FSES, we collected data on the level of education of the parents as an objective indicator. Parental Education has been reported to be strongly associated with self-esteem ( 37 ), perceived stress, and peer relationships. In this study, level of education was defined as the years of education.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adrijana Berčić, Inja Erceg found that parental behavior characterized by high involvement, the manifestation of care and love, adequate control does not undermine the autonomy of children, does not cause destructive effects, like other types of parental control [32]. Studying the relationship between the subjective socio-economic status of families and life satisfaction among adolescents by scientists Yan Wenjing, Yang Kairong, Wang Qiuling established close correlations, as well as factors mediating on them: self-esteem and social support [7]. These results provide an indirect confirmation that the attitude towards "the world is benevolent" and "the self-image" can be predictors of the formation of a subjective assessment of social status in children and young people.…”
Section: Itse-2020mentioning
confidence: 99%
“…Subjective social status (hereinafter referred to as SSS) refers to a person's perception of their position or rank in relation to others, and for young people, status is usually defined in the context of society or school [2]. Theoretical analysis of studies of subjective social status shows that it is most often considered in such aspects as the relationship of SSS with physical and mental health [2][3][4][5][6], the influence of family economic wealth and well-being on the formation of SSS [1,[7][8][9][10], the level of education and training [8,[11][12][13][14], professional and labor activity, employment or unemployment [5,13,[15][16], age [3,5,17,18], national, ethnic [18][19][20], racial [20,21], class [1,22] and gender [3,16,20], valuesemantic sphere [23][24][25] and motivational sphere [26].…”
Section: Introductionmentioning
confidence: 99%